A STUDY ON VARIOUS E-RECRUITMENT TOOLS AND ITS EFFECTIVENESS FOR RECRUITMENT - Gulomkodirova , Mamura Saydumarxon qizi (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
E-recruitment refers to the use of web-based technology for the different processes of drawing in, assessing, selecting, recruiting and onboarding candidates. Through E-recruitment employers reach a larger number of potential employees. With the adoption of technology and Internet penetration by employers in the future, the growth of the e-recruitment industry has been promoted. Turning to the online recruitment process, the organization has reduced the cost of the traditional recruitment model by nearly 80%. Here in this study descriptive research design is adopted. The objective of any recruitment is to recruit the right candidate for the right slot. The means of recruitment is also equally important. Keeping the current trends in view, emphasizing on E-recruitment is essential and ideal for effective and efficient recruitment. The days of manual recruitment are fading away gradually as organizations are moving to E- recruitment. E- Recruitment is here to stay.